PENERAPAN PENILAIAN ACUAN NORMA (PAN) PADA PELAJARAN SENI BUDAYA/MUSIK DI KELAS VII-G SMP NEGERI I 2 X 11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Chloriana, Wahyu; Sudarman, Yos (SENDRATASIK UNP, 2019)
AbstractÂ The Research aims to explain the implementation of PAN on the cultural / music art learning at class VII-G SMP Negeri 1 2x11 Enam Lingkung Padang Pariaman regency. The type of this research was qualitative research with using analysis descriptive method. By using this research method, the object of assessment in the form of teacher activities on implementing PAN and assessment of the students learning outcomes is observed and the researcher is also involved in discussing it with the teacher. The main instrument used in this research was the researcher and it was supported by interview, observation, and library study. The result of this study shows that by using PAN, the student learning outcomes can be known and improved based on their students' abilities. Increasing the learning outcomes can be achieved because the value of the class average is rising from 70 to 77. It indicates that the students learn to improve their learning outcomes together. As long as the PAN is carried out, the teacher continues to motivate the students become active and excited in learning.Â Keywords: PAN, class average, cultural art learning/Music